ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DI KOTA CILEGON - Alief Nazwa Alam; Ahmad Sururi (Jurnal Menara, 2026)
Taxes are crucial as a primary source of state and regional revenue, particularly in supporting national development and regional fiscal independence. However, the low level of motor vehicle taxpayer compliance in Cilegon City is a strategic issue that requires further study. This study aims to analyze the influence of tax socialization, tax sanctions, taxpayer awareness, and service quality on the level of motor vehicle taxpayer compliance in Cilegon City, Banten Province. This study uses a quantitative approach with the path analysis method. Samples were taken from motor vehicle taxpayers in Cilegon City, and data were collected through questionnaires. The results show that the variables of tax socialization, tax sanctions, and service quality do not significantly influence taxpayer compliance, as indicated by the T-statistic values ​​of 0.612; 1.347; and 0.530, respectively (smaller than the T-table of 1.653). Conversely, taxpayer awareness has a positive and significant influence on compliance, with a T-statistic value of 2.376 (greater than the T-table). These findings indicate that increased compliance among motor vehicle taxpayers in Cilegon City is more influenced by individual awareness than by socialization, sanctions, or service quality. Therefore, compliance improvement strategies should focus on building tax awareness through ongoing education and a participatory approach.